Peningkatan Kemampuan Menulis Cerita Menggunakan Metode Picture And Picture Pada Siswa Madrasah Ibtidaiyah - Rachman, Fatchur; BS., Abdul Wachid (QUALITY, 2021)
The purpose of this study is to improve the ability to write stories in students of Madrasah Ibtidaiyah (MI). This research was conducted at MIM Pangempon using picture and picture as the method. The research conducted is in the form of classroom action research or commonly abbreviated as CAR. This research is divided into two cycle stages, each stage of this cycle consists of planning, implementing actions, observing, and reflecting. As the subject in the classroom action research, the 4th grade students of MIM Pangempon, Kejobong District, Purbalingga Regency with a total of 10 students. Based on the results of this study, a conclusion can be drawn that learning to write stories for fourth grade students at MI Muhammadiyah Pangempon uses the picture method. and picture can improve students' abilities. This increase can be proven from the results obtained by students, namely before the action was 40%, then in the first cycle it increased to 60%, and in the second cycle it increased again to 90%.